Comparative Study of Disturbance Observer-Based Control Methods on an Industrial Gimbal System - Mucahid Ridvan Kaplan; Burak Kurkcu; Mehmet Onder Efe; Zeki Yagiz Bayraktaroglu (IEEE Access, 2025)
Disturbance-observer-based control (DOBC) methods are developed to approximate the closed-loop behavior of dynamic systems to the nominal system response determined during the design phase. In the literature, many different approaches have been derived for similar purposes. This paper presents a comprehensive experimental evaluation of notable DOBC structures, conducted in both a simulation environment with a comparative analysis and in real-time experiments. Unlike previous studies, which predominantly focus on theoretical analysis or simulation-based assessments, this study provides a systematic experimental comparison of DOBC methods implemented on a gimbal platform, offering insights into their practical performance. For this purpose, the mathematical representations of the DOBC methods have been rearranged in an application-oriented framework and employed for high-precision control of a gimbal platform. A dedicated simulation environment has been established to enable a proper comparison of the proposed DOBC methods in terms of applicability and performance evaluations, considering well-defined and measurable metrics within the experimental setup. The control system designs based on the methods evaluated in this paper were carried out in line with the original studies as originally suggested. The results of the investigation are interpreted using both time- and frequency-domain metrics, highlighting the practical implications of DOBC methods in real-world applications.